Sigmoid volvulus: an uncommon complication of Hirschsprung's disease - Ranjan, Abhishek (BMJ Case Rep, 2016)
Sigmoid volvulus is a rare and potentially life-threatening condition that is usually seen in adults, however, when diagnosed in children, it is often associated with Hirschsprung's disease (HD). We report a case of an 11-year-old boy who presented with a history of constipation since 1.5 months of age, with acute onset of severe abdominal pain and marked distention of the abdomen. Sigmoid volvulus was suspected, detected and successfully managed with resection of the sigmoid colon and primary Scott Boley's pull-through. This report underscores the importance of suspecting sigmoid volvulus in the pertinent clinical setting; also, a primary definitive procedure can be performed in select cases.